2014
DOI: 10.1111/1471-0528.12630
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and childbirth outcomes among adolescent mothers: a World Health Organization multicountry study

Abstract: Objective: To investigate the risk of adverse pregnancy outcomes among adolescents in 29 countries. Design: Secondary analysis using facility-based cross-sectional data of the World Health Organization Multicountry Survey on Maternal and Newborn Health. Setting: Twenty-nine countries in Africa, Latin America, Asia and the Middle East. Population: Women admitted for delivery in 359 health facilities during 2-4months between 2010 and 2011. Methods: Multilevel logistic regression models were used to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
781
20
54

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 797 publications
(910 citation statements)
references
References 31 publications
55
781
20
54
Order By: Relevance
“…Premature rupture of membranes has been attributed to biological immaturity of the uterus as well as the shortness of the cervix, which leads to increase the risk of ascending infections and PROM, which may be due to poor hygiene in this group of women [9]. The prevalence of PIH and PET in early teenagers was nearly double that observed in late teenagers (25.0 vs. 11.8 %, and 15.0 vs. 7.7 %, respectively), although this difference did not reach statistical significance, those obstetric complication should be diagnosed and managed early during pregnancy in those very young mothers who may not realize the seriousness of this problem, others reported similar findings [10]. Obstetric complications such as PPH, oligohydramnios, and polyhydramnios were similar in the two groups, so maternal ages did not show any influence on the prevalence of such complications [11].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Premature rupture of membranes has been attributed to biological immaturity of the uterus as well as the shortness of the cervix, which leads to increase the risk of ascending infections and PROM, which may be due to poor hygiene in this group of women [9]. The prevalence of PIH and PET in early teenagers was nearly double that observed in late teenagers (25.0 vs. 11.8 %, and 15.0 vs. 7.7 %, respectively), although this difference did not reach statistical significance, those obstetric complication should be diagnosed and managed early during pregnancy in those very young mothers who may not realize the seriousness of this problem, others reported similar findings [10]. Obstetric complications such as PPH, oligohydramnios, and polyhydramnios were similar in the two groups, so maternal ages did not show any influence on the prevalence of such complications [11].…”
Section: Discussionmentioning
confidence: 58%
“…These findings are supported by others, this may be due to the presence of more functional myometrium, greater connective tissue elasticity, and lower cervical compliance that allowed for more spontaneous vaginal deliveries in young age group [4,7]. Five minutes Apgar score, which is more relevant in assessing newborn health was similar in the two groups, 5 min Apgar score considered as a predictor for postneonatal hospitalization, a Canadian study showed that with decreasing of 5 min Apgar score, the risk of hospitalization in the first 10 years of life is increased [10]. During pregnancy, early and late teenage women attended antenatal clinics at a tertiary teaching hospital and any obstetric complication which may affect prenatal outcomes was diagnosed and managed immediately, this resulted in very low prenatal mortality rates in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely adolescent parenthood predicts both poor maternal and infant health. In over 120,000 pregnancies in girls aged 10-24 in the Multicountry Survey of Maternal and Child Health of the World Health Organization (WHO), those giving birth before 15 years of age were at higher risk of eclampsia and puerperal infection 27 . Their babies had higher rates of low birth weight, preterm delivery and severe neonatal conditions 27 .…”
Section: Early Parenthood and Its Consequencesmentioning
confidence: 99%
“…In over 120,000 pregnancies in girls aged 10-24 in the Multicountry Survey of Maternal and Child Health of the World Health Organization (WHO), those giving birth before 15 years of age were at higher risk of eclampsia and puerperal infection 27 . Their babies had higher rates of low birth weight, preterm delivery and severe neonatal conditions 27 . Similarly, in pooled analyses of 19,403 offspring from birth cohorts in Brazil, Guatemala, India, the Philippines and South Africa, giving birth before the age of 19 predicted low birth weight, preterm birth and stunting of offspring and these associations were strongest in the youngest mothers 28 .…”
Section: Early Parenthood and Its Consequencesmentioning
confidence: 99%
“…Teenage pregnancy is a concern worldwide as it is associated with low birth weight (LBW) and preterm birth (PTB) [2][3][4]. Pregnancy in teenagers can result in adverse maternal outcome such as severe anemia or death and compromise their socio-economic opportunities [5].…”
Section: Introductionmentioning
confidence: 99%